Regional Economic Outlook, Fall 2006, Sub-Saharan Africa, Supplement. (Regional Economic Outlook, 2006)
Provides a broad synopsis of recent economic developments in the Middle East and Central Asia region, highlighting common trends and policies among countries in the region, and reviewing prospects and policies for the coming year. Includes a statistical appendix.